2021
DOI: 10.3390/foods10081930
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content, Main Flavonoids, and Antioxidant Capacity of Instant Sweet Tea (Lithocarpus litseifolius [Hance] Chun) Prepared with Different Raw Materials and Drying Methods

Abstract: This study aims to investigate the effects of raw materials and drying methods on the phytochemical and antioxidant capacities of instant sweet tea powder. Four raw materials of sweet tea leave powders (STUT) were extracted and dried with two methods (freeze-drying and spray-drying). The antioxidant capacity, total phenolic content (TPC), total flavonoid content (TFC), and phlorizin and trilobatin contents of obtained instant sweet tea powders were compared. In addition, the single-factor experiments coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Significant changes in phenolic composition and antioxidant activity were found in the 17 edible seeds and sprouts, the reason might be associated with the initiation of endogenous enzymes and complicated biochemical metabolism ( 17 ). However, some samples with higher TPC have lower antioxidant capacity, this could be explained by the fact that some other compounds in extracts influence the responses of the FRAP, ABTS, and DPPH reagents, and this similar results was observed in previous studies ( 15 , 25 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Significant changes in phenolic composition and antioxidant activity were found in the 17 edible seeds and sprouts, the reason might be associated with the initiation of endogenous enzymes and complicated biochemical metabolism ( 17 ). However, some samples with higher TPC have lower antioxidant capacity, this could be explained by the fact that some other compounds in extracts influence the responses of the FRAP, ABTS, and DPPH reagents, and this similar results was observed in previous studies ( 15 , 25 ).…”
Section: Discussionsupporting
confidence: 84%
“…All the contents were finally corrected with the dilution fold finally. The TPC was detected by Folin–Ciocalteu method described previously with a little modification ( 15 ), and the absorbance at 760 nm was determined. Finally, the TPC of seed or sprout was expressed as mg gallic acid equivalent (GAE)/100 g DW.…”
Section: Methodsmentioning
confidence: 99%
“…The assays of FRAP and TEAC were used to evaluate the antioxidant activities of kombucha beverages. These assays were performed based on the published literature [ 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then the mixture was centrifuged at 4200× g for 8 min, and the supernatant was collected and concentrated at 45 °C under vacuum and then freeze-dried to obtain STE. The total phenolic content (TPC) was determined by the Folin–Ciocalteu assay in gallic acid equivalents (GAEs), and the total flavonoid content (TFC) was determined as described previously [ 10 ]. In addition, the main phytochemical components of STE were identified and quantified by high-performance liquid chromatography (HPLC) analysis equipped with an Agilent Zorbax SB-C18 column (4.6 × 150 mm, 5 µm) by comparing the retention time with standards [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lithocarpus litseifolius (Hance) Chun, commonly known as sweet tea, is a new food resource with both medicinal and edible functions [ 9 ]. There is a long history of sweet tea being used as herbal tea or traditional medicine to prevent diabetes, hypertension, and hyperlipidemia [ 10 ]. Modern studies have indicated that those effects are mainly associated with its main bioactive dihydrochalcones, especially phlorizin, phloretin, and trilobatin [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%